2014
DOI: 10.1038/nature13261
|View full text |Cite|
|
Sign up to set email alerts
|

CFIm25 links alternative polyadenylation to glioblastoma tumour suppression

Abstract: The global shortening of mRNAs through alternative polyadenylation (APA) that occurs during enhanced cellular proliferation represents an important, yet poorly understood mechanism of regulated gene expression1,2. The 3′UTR truncation of growth promoting mRNA transcripts that relieves intrinsic microRNA- and AU-rich element-mediated repression has been observed to correlate with cellular transformation3; however, the importance to tumorigenicity of RNA 3′ end processing factors that potentially govern APA is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
524
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(561 citation statements)
references
References 39 publications
34
524
3
Order By: Relevance
“…However, a recent report introduced CFIm25 as a tumor suppressor in glioblastoma, negatively regulating the expression of GLS via 3UTR processing. 9 Although it may initially seem contradictory to our findings, it has been reported that CCAT2 is not expressed in glioblastoma cell lines. This suggests that interaction with the lncRNA may modulate the function of the protein in a cell-specific way.…”
contrasting
confidence: 99%
“…However, a recent report introduced CFIm25 as a tumor suppressor in glioblastoma, negatively regulating the expression of GLS via 3UTR processing. 9 Although it may initially seem contradictory to our findings, it has been reported that CCAT2 is not expressed in glioblastoma cell lines. This suggests that interaction with the lncRNA may modulate the function of the protein in a cell-specific way.…”
contrasting
confidence: 99%
“…To determine whether reduced U1 snRNA levels in our snRNP biogenesis mutants correlated with expression of shorter mRNAs, mapped RNA-seq reads were analyzed using the DaPars linear regression algorithm (Masamha et al 2014;Xia et al 2014). DaPars output is displayed as a percentage of distal poly(A) site usage index (PDUI) for each transcript, or as the difference in the PDUI value between wild-type and mutant (ΔPDUI).…”
Section: Snrnp Biogenesis Mutants Exhibit a Trend Toward Shorter Mrnasmentioning
confidence: 99%
“…Altered expressions of CPSF and CFIm complex members have also been implicated in the selection of alternate poly(A) signals in normal physiological settings including self-renewal of embryonic stem cells and in disease states (reviewed in Zheng & Tian 2014). For example, decreased CFIm25 expression correlated with 3′-UTR shortening events in glioblastoma patients (Masamha et al 2014). Furthermore, a combinatorial approach of computation and experimentation revealed a pattern of 3′-UTR length changes in breast cancer patients/cells and a potential link between APA, CSTF2, and EGF (epidermal growth factor) signaling (Akman et al 2015).…”
Section: Role Of Rbps In Apa Decisionsmentioning
confidence: 99%